2020
DOI: 10.1063/5.0020244
|View full text |Cite
|
Sign up to set email alerts
|

Probing the trap states in N–i–P Sb2(S,Se)3 solar cells by deep-level transient spectroscopy

Abstract: In this study, we provide fundamental understanding on defect properties of the Sb2(S,Se)3 absorber film and the impact on transmission of photo-excited carriers in N–i–P architecture solar cells by both deep level transient spectroscopy (DLTS) and optical deep level transient spectroscopy (ODLTS) characterizations. Through conductance–voltage and temperature-dependent current–voltage characterization under a dark condition, we find that the Sb2(S,Se)3 solar cell demonstrates good rectification and high temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…E Fn and E Fp are the quasi-Fermi levels in the N-type and P-type materials. [55,56] Also, the V OC is affected by the selectivity of the electron transport layer and the hole transport layer, which is mainly determined by the energetics and transport properties of the carrier transport material, including the band alignment, the charge mobility and the surface dipoles. Therefore, the ideal electron transport materials (ETMs) and hole transport materials (HTMs) can significantly reduce the interfacial recombination, which can directly affect V OC through the presence of surface defects/traps.…”
Section: Interface-induced Recombination In Sb 2 X 3 Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…E Fn and E Fp are the quasi-Fermi levels in the N-type and P-type materials. [55,56] Also, the V OC is affected by the selectivity of the electron transport layer and the hole transport layer, which is mainly determined by the energetics and transport properties of the carrier transport material, including the band alignment, the charge mobility and the surface dipoles. Therefore, the ideal electron transport materials (ETMs) and hole transport materials (HTMs) can significantly reduce the interfacial recombination, which can directly affect V OC through the presence of surface defects/traps.…”
Section: Interface-induced Recombination In Sb 2 X 3 Solar Cellsmentioning
confidence: 99%
“…Lian et al also detected Sb S antisite defects by DLTS and O-DLTS, with the trap levels of 0.52 and 0.76 eV, respectively. [56] Additionally, the H1 and H2 are both deep level defects due to their large distance from the VBM. They could act as recombination centers to pin the Fermi level and result in V OC deficit.…”
Section: Defect-assisted Recombination In Sb 2 X 3 Solar Cellsmentioning
confidence: 99%
“…Up to now, many processes have been developed to improve the film quality of antimony chalcogenide, especially the close-spaced sublimation (CSS) technique and the hydrothermal approach, which have made major breakthroughs successively in recent years. , Contrastingly, rare research studies of device configuration were reported, and the commonly applied device configurations were almost focused on conventional sensitized device configuration and planar heterojunction device structures . Also, because of the Shockley–Queisser radiative efficiency limits, the theoretical PCE of antimony chalcogenide single-junction solar cells is limited to ∼32%, which further constrains the improvement of the device performance. , Therefore, the multijunction structure could be a preferred strategy to broaden the theoretical limits by facilitating the efficient utilization of the spectral energy . This strategy has already been widely used in various thin film solar cells and achieves a higher PCE, which exceeds the Shockley–Queisser limit of single-junction solar cells. , Nevertheless, there were a few reports on antimony chalcogenide multijunction solar cells because of the current immature fabrication process, particularly the deposition of high-quality Sb 2 (S,Se) 3 films with desirable band gaps.…”
Section: Introductionmentioning
confidence: 99%
“…Lian et al in 2020 224 conduced a detailed temperature dependent study on an n-i-p structured FTO/CdS/ Sb 2 (S,Se) 3 /Spiro-OMeTAD/Au device. The Sb 2 (S,Se) 3 film was synthesized using the hydrothermal method, and the device exhibited a PCE of 8.6%, V oc of 0.64 V, J sc of 21.9 mA cm −2 , and FF of 61.5%.…”
Section: T H Imentioning
confidence: 99%